CAN SHIFT TO A FUNDED PENSION SYSTEM AFFECT NATIONAL SAVING? THE CASE OF ICELAND - BONASIA, Mariangela; NAPOLITANO, Oreste (Theoretical and Practical Research in Economic Fields; Vol 1 No 1 (2010): TPREF, Volume I, Issue 1(1), Summer 2010, 2010)
Across industrialised and developing countries public pension systems have been heavily reformed during the last two decades. The major concern relates the financial sustainability of pay-as-you-go pension schemes. The proposals to privatize social security lead to the creation of a multipillar system. This study assesses the validity of the effect of pension reforms on domestic savings in two steps: first, to test for the existence of a long-run relationship, we use an ARDL model; second, we employ the Kalman filter algorithm, in order to recover the parameter dynamics overtime. We analyse the case of Iceland because its pension system is characterized by a large mandatory private pillar. The empirical evidence supports the widely held view that growing mandatory pension funds financial assets has significantly positive impact on national saving. Moreover, we show that the pattern of the pension funds’ coefficients seems to capture well the economic dynamic of the period. The coefficients of the funded pillars illustrate a shift upward soon after the launch of the reforms in 1998. Later on, these coefficients show a negative trend till the middle of 2004 and they increase sharply until the beginning of 2006. Afterwards, following the Icelandic and international financial crisis, they strongly declines.